Development of Anther Culture Protocol for Selected Brinjal Germplasm (Solanum melongena L.) (Plant Tissue Culture and Biotechnology, 2025)
Selected anthers from seven brinjal germplasm namely; Anjalee, Padagoda, EGH-5, EGH-13, EGH-16, V-5, and 8104 were cultured on MS medium containing different hormonal supplements for callus induction and in vitro regeneration. Various hormonal treatments (T1 to T4) for callus induction consisted 1.0 mg/l Kn and 2.0 mg/l BAP with different concentrations (1, 3, 5 and 0 mg/l) of NAA. The highest percentage of callus induction (83.33 ± 16.67, p